Teacher Quality and Student Achievement - Darling-Hammond, Linda (Education Policy Analysis Archives, 2000)
Using data from a 50-state survey of policies, state case study analyses, the 1993-94 Schools and Staffing Surveys (SASS), and the National Assessment of Educational Progress (NAEP), this study examines the ways in which teacher qualifications and other school inputs are related to student achievement across states. The findings of both the qualitative and quantitative analyses suggest that policy investments in the quality of teachers may be related to improvements in student performance. Quantitative analyses indicate that measures of teacher preparation and certification are by far the strongest correlates of student achievement in reading and mathematics, both before and after controlling for student poverty and language status. State policy surveys and case study data are used to evaluate policies that influence the overall level of teacher qualifications within and across states. This analysis suggests that policies adopted by states regarding teacher education, licensing, hiring, and professional development may make an important difference in the qualifications and capacities that teachers bring to their work. The implications for state efforts to enhance quality and equity in public education are discussed.